European Food Safety Certification - The GlobalG.A.P® Standard and Its Accredited Certification Scheme - Richard C. Yudin; Keith R. Schneider (EDIS, 2012)
Many European importers and retailers will only buy produce, meat, and grain-based products that come from GlobalG.A.P-certified farms. Despite its environmental origins, the main concern is food safety, followed by worker welfare, and then ecological matters. There are slightly different versions for fresh fruit and vegetables, meat products, flowers and ornamentals, and combinable crops (grains and pulses). There is also an Integrated Farm Assurance version for farms with several types of operations taking place at once. This revised 4-page fact sheet was written by Richard C. Yudin and Keith R. Schneider, and published by the UF Department of Food Science and Human Nutrition, February 2012.